GENETIC POTENTIAL OF APPLE-TREE BREEDING IN THE SOUTH OF WEST SIBERIA - S. A. Makarenko; I. P. Kalinina (Труды по прикладной ботанике, генетике и селекции)
The results of apple breeding in the south of West Siberia according to the main economically useful features are presented in the paper. On the basis of hybridological analysis, 30 donors and sources of high winter hardiness, 16 sources of polygenic scab resistance and 13 heterozygous sources of monogenic resistance as well as productive varietal samples for breeding for yield and high fruit quality have been selected. Brief characteristics of 34 apple varieties of Gorno-Altaisk breeding are given.